Seasonal response of Asian monsoonal climate to the Atlantic Multidecadal Oscillation - Wang, Yanming; Li, Shuanglin; Luo, Dehai (Journal of Geophysical Research: Atmospheres, 2009)
The influence of the Atlantic Multidecadal Oscillation (AMO) on Asian monsoonal climate in all four seasons is investigated by comprehensive observational analyses and ensemble experiments with atmospheric general circulation models (AGCMs). Three AGCMs are forced by prescribed climatological seasonal cycle of sea surface temperature (SST) or with additional SST anomalies representing the warmth phase of the AMO. The results in both the observations and the models consistently suggest that the warm AMO phase gives rise to elevated air temperatures in East Asia and northern India but decreased air temperatures in much of central‐southern India in all four seasons. This positive AMO anomaly also causes more rainfall in central and southern India in every season, particularly in summer and fall. In contrast, the sign of AMO influences on East Asian rainfall is season‐dependent: in southeastern China, it induces increased rainfall in summer but suppressed rainfall in autumn. It is suggested that these AMO influences are realized by warming Eurasian middle and upper troposphere in all four seasons, resulting in weakened Asian winter monsoons but enhanced summer monsoons. Furthermore, the formation of the troposphere heating anomaly may be related to the wave guidance mechanism associated with the Asian upper jet.